Management Of Intervertebral Disc Inflammation Following Resection Of Lumbar Disc Herniation A Study Conducted At Tishreen University Hospital - علي محمد (Latakia University Journal -Medical Sciences Series, 2023)
Background: The aim of the study was to retrospectively evaluate the outcome of medical management of postoperative discitis . Materials and Methods: A total of 31 patients treated for postoperative discitis were included in the study. Clinical, radiological, and laboratory data of all patients were collected and evaluated. All patients were treated initially with bed rest and antibiotic therapy after radiological diagnosis. Surgical management was undertaken after failure of 4 weeks of conservative management. All cases were followed clinically with laboratory and radiological investigations. Results: Five cases failed to respond to medical management and were treated surgically with debridement and transpedicular fixation. All patients showed clinical recovery till the last follow-up. Conclusion: Early diagnosis and proper management are the keys to successful outcome of postoperative spndylodiscitis. Surgical debridement and fusion are required when conservative treatment fails.